Immunotherapeutic strategies for invasive bladder cancer: a comprehensive review - Wang, Yingying; He, Min; Li, Jian; Li, Li (Frontiers in Immunology, 2025)
Bladder cancer is a prevalent malignancy, with muscle-invasive bladder cancer (MIBC) presenting a significant therapeutic challenge. Standard treatments, including radical cystectomy (RC) and neoadjuvant chemotherapy, pose substantial risks and impact quality of life, leading to increasing interest in bladder-preserving therapies (BPT). Immunotherapy has revolutionized bladder cancer management, with strategies ranging from intravesical Bacillus Calmette-Guérin (BCG) to immune checkpoint inhibitors targeting programmed cell death protein 1 (PD-1) and its ligand (PD-L1). In BCG-unresponsive non-muscle-invasive bladder cancer (NMIBC), PD-1 inhibitors such as pembrolizumab offer promising response rates. In MIBC, neoadjuvant immunotherapy with agents like atezolizumab and pembrolizumab improves pathological complete response (pCR) and facilitates bladder preservation. Combination regimens integrating radiotherapy, chemotherapy, and immunotherapy not only enhance treatment efficacy but also exploit mechanisms such as immunogenic cell death and antigen release that further augment antitumor immune responses. This review provides a comprehensive analysis of current immunotherapeutic strategies for invasive bladder cancer, highlighting their clinical applications and future potential.